2023
DOI: 10.3390/ijms241814233
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of CRISPR/Cas Systems for Precise Genome Editing

Magdalena Hryhorowicz,
Daniel Lipiński,
Joanna Zeyland

Abstract: The bacteria-derived CRISPR/Cas (an acronym for regularly interspaced short palindromic repeats/CRISPR-associated protein) system is currently the most widely used, versatile, and convenient tool for genome engineering. CRISPR/Cas-based technologies have been applied to disease modeling, gene therapies, transcriptional modulation, and diagnostics. Nevertheless, some challenges remain, such as the risk of immunological reactions or off-target effects. To overcome these problems, many new methods and CRISPR/Cas-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…The impact of off-target effects on CRISPR-Cas13a technology was further reduced. Studies have also shown that Cas13a can tolerate single nucleotide mismatch between crRNA and target sequence, but double mismatch can significantly reduce the cleavage efficiency of Cas13a enzyme (Hryhorowicz et al, 2023).…”
Section: Summary and Prospectmentioning
confidence: 99%
“…The impact of off-target effects on CRISPR-Cas13a technology was further reduced. Studies have also shown that Cas13a can tolerate single nucleotide mismatch between crRNA and target sequence, but double mismatch can significantly reduce the cleavage efficiency of Cas13a enzyme (Hryhorowicz et al, 2023).…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Each CRISPR-Cas locus includes a strain-specific array of so-called spacer sequences, which can be used for strain subtyping [17]. CRISPR-Cas systems can be divided into six major types (I-VI) and several subtypes (A-I, K, U) based on a combination of evidence from phylogenetic, comparative genomic, and structural analysis [18,19]. 'UNKN' in this column denotes an incomplete system, in which some genes are absent, while 'NF' indicates that CRISPR-Cas system was not revealed in a particular isolate genome.…”
Section: Typing Summary Tablementioning
confidence: 99%
“…Cas9 uses two nuclease domains: a well-conserved RuvC domain consisting of three split RuvC motifs and an HNH domain residing in the middle of the protein. Each domain cleaves one strand of the target dsDNA at a specific 3-bp site of the NGG PAM sequence to produce a predominantly blunt-ended double-strand break (DSB) [28,29].…”
Section: Molecular Mechanism Of the Crispr/cas9 Systemmentioning
confidence: 99%